1995
DOI: 10.1074/jbc.270.10.5115
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Biological Specificity of Cystatin C

Abstract: The structural basis for the biological specificity of human cystatin C has been investigated. Cystatin C and other inhibitors belonging to family 2 of the cystatin superfamily interact reversibly with target peptidases, seemingly by independent affinity contributions from a wedge-shaped binding region built from two loop-forming inhibitor segments and a binding region corresponding to the N-terminal segment of the inhibitor. Human cystatin C variants with Gly substitutions for residues Arg-8, Leu-9, and/or Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 47 publications
9
85
0
3
Order By: Relevance
“…Это обусловлено тем, что цистатин С, синтезируемый всеми ядерными клетками, свободно фильтруется через клубочковую мембрану и полностью метаболизируется после его реабсорбции в проксималь-ных канальцах и в настоящее время, по данным литерату-ры [11], является показателем функции почек.…”
Section: Discussionunclassified
“…Это обусловлено тем, что цистатин С, синтезируемый всеми ядерными клетками, свободно фильтруется через клубочковую мембрану и полностью метаболизируется после его реабсорбции в проксималь-ных канальцах и в настоящее время, по данным литерату-ры [11], является показателем функции почек.…”
Section: Discussionunclassified
“…This contrasts with the inhibitory specificities of cystatins C and E/M, which both have the capacity to inhibit cathepsin B (Table I). A structural element that has been shown to be at least partly responsible for the target enzyme specificity of cystatin C and of crucial importance for efficient cystatin C binding of cathepsin B is the N-terminal segment with ArgLeu-Val-Gly at positions 8 -11 (40,53). Leu-9 and Val-10, interacting with target enzyme substrate subpockets S 3 and S 2 , respectively, are especially important for a fast interaction between the cystatin and cathepsin B (54,55).…”
Section: Resultsmentioning
confidence: 99%
“…Enzyme Assays-The methods used for active-site titration of papain (using benzoyl-DL-Arg p-nitroanilide (Bachem Feinchemikalien, Bubendorf, Switzerland) as substrate), titration of the molar enzyme inhibitory concentration in cystatin F preparations, and determination of equilibrium constants for dissociation (K i ) of complexes between cystatin F and cysteine proteinases have been reviewed (1). The enzymes used were papain (EC 3.4.22.2; from Sigma), activatable to 70 -75% after affinity purification on Sepharose-coupled Gly-Gly-Tyr-Arg as detailed previously (39,40), human cathepsin B (EC 3.4.22.1; from Calbiochem, La Jolla, CA), and human cathepsin L (EC 3.4.22.15; Calbiochem). The fluorogenic substrate used for K i determinations was benzyloxycarbonyl-Phe-Arg-7-amido-4-methylcoumarin (10 M; Bachem Feinchemikalien), and the assay buffer was 100 mM sodium phosphate buffer (adjusted to pH 6.5 for papain and to pH 6.0 for cathepsin B and cathepsin L) containing 1 mM dithiothreitol and 2 mM EDTA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heating the polymannosylated protein at 95³C for 30 min resulted in less than 40% reduction of the papain-inhibiting activity. Although it is reported that cystatin C is resistant to heating due to the tightly packed conformation [15], further enhancement of the thermostability was observed in the polymannosylated cystatin.…”
Section: Molecular Stability Of Polymannosylated Cystatinmentioning
confidence: 99%